2022
DOI: 10.1136/jim-2022-002398
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends and Disparities in Gastroenterology Care use before, during, and after COVID-19 Lockdown

Abstract: Socioeconomic disparities adversely affected healthcare use during COVID-19 lockdown. However, trends in these disparities post lockdown are unknown. Therefore, our aim was to study temporal trends and factors associated with gastroenterology healthcare access and disparities during and after COVID-19 lockdown. This cohort study consisted of patients receiving outpatient care in the Cleveland Clinic gastroenterology department between March 2020 and June 2020 and corresponding time periods in 2019 and 2021. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…demonstrated that Black and underinsured patients had worse outcomes and greater resource utilization in non-variceal UGIB [19]. Disparity in care for vulnerable populations has been shown to be widespread in medicine and prevalent amongst diverse specialties and subspecialties [14,[20][21][22]. These studies have included elderly patients as a group with worse outcomes but have typically associated these outcomes with underlying comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that Black and underinsured patients had worse outcomes and greater resource utilization in non-variceal UGIB [19]. Disparity in care for vulnerable populations has been shown to be widespread in medicine and prevalent amongst diverse specialties and subspecialties [14,[20][21][22]. These studies have included elderly patients as a group with worse outcomes but have typically associated these outcomes with underlying comorbidities.…”
Section: Discussionmentioning
confidence: 99%